Impact of health facilities on malaria control interventions among children under five years of age and pregnant women in Nigeria - Aregbeshola, Bolaji Samson; Khan, Samina Mohsin (South East Asia Journal of Public Health, 2017)
Malaria is still one of the biggest public health problems in Nigeria in spite of numerous control interventions against the disease as well as access to and availability of medicines to address it. The children under five years of age and pregnant women are household members that are most at risk of this disease. The study aims to examine the impact of health facilities on malaria control interventions. Secondary data from Nigeria Demographic and Health Survey 2013 was utilized to investigate the impact of type of health facility visited on malaria control interventions. Variables on malaria control interventions such as malaria prevention in pregnancy, antimalarial drugs and rapid diagnostic testing were analysed. Chi square analysis was used to test for association between variables at 0.05 level of significance. The number of dose of Intermittent Preventive Treatment in Pregnancy (IPTp) taken during pregnancy was associated with private hospital/clinic, government health post and government hospital. The type of antimalarial drug used was associated with the type of health facility visited by children under 5 years. Rapid diagnostic tests (RDTs) for children under 5 years of age was associated with government hospital, government health centre, private hospital/clinic, chemist/patent medicine store and other private medical sector. Our study concludes that the type of health facility visited has an impact on malaria control interventions in Nigeria. There is a need for political actors and policy makers to improve the standard of health care facilities across the country in order to engender the provision of adequate health service delivery to the children under 5 years of age and pregnant women. South East Asia Journal of Public Health Vol.7(1) 2017: 35-41